Englisch als Lingua franca versus andere Sprachen im Bildungswesen: Polen und Japan im Vergleich - Kowalonek-Janczarek, Monika (Glottodidactica, 2019)
The purpose of this study is to compare Poland’s and Japan’s foreign language policies in preschool, elementary, lower/upper secondary and higher education and shed light on the aspect of multilingualism in this milieu as well. Based on secondary data (ministerial ordinances, governmental reports, curricula) and literature knowledge, the paper provides a comparative overview of the Polish and Japanese contexts which differ in a strong way. While Poland’s foreign language policy is mainly based on the objectives of the EU’s policy according to which every European citizen should master two other languages in addition to his or her mother tongue, the Japanese government’s policy aims at improving English education.